Assessing water resource use in livestock production: A review of methods - Ran, Ylva; Lannerstad, Mats; Herrero, Mario; Middelaar, Corina E.M. van; Boer, Imke J.M. de (Elsevier, 2016)
This paper reviews existing methods for assessing livestock water resource use, recognizing that water plays a vital role in global food supply and that livestock production systems consumes a large amount of the available water resources. A number of methods have contributed to the development of water resources use assessments of livestock production. The methods reviewed in this study were classified into three categories: water productivity assessments, water footprint assessments and life cycle assessments. The water productivity approach has been used to assess benefits derived from consumptive water use in livestock production; the water footprint approach has raised awareness of the large amounts of water required for livestock production; and life cycle assessments highlight the important connection between water resource use and local impacts. For each of the methods we distinguish strengths and weaknesses in assessing water resource use in livestock production. As a result, we identify three key areas for improvement: 1) both green and blue water resources should be included in assessments, and presented separately to provide informative results; 2) water quality should not be summarized within quantitative assessments of water resource use; and 3) methods for assessing water use in livestock systems must consider the alternative uses, multiple uses and benefits of a certain resource in a specific location.